Acupuncture combined with repetitive transcranial magnetic stimulation for the treatment of post-stroke cognitive impairment: a systematic review and meta-analysis with trial sequential analysis - Zhang, Xiaomeng; Wang, Jie; Pan, Wen; Sun, Jin; He, Mingna; Wang, Qinyun; Sun, Peiyang (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to comprehensively evaluate the clinical effectiveness and safety of acupuncture combined with repetitive transcranial magnetic stimulation (rTMS) in treating post-stroke cognitive impairment (PSCI) through meta-analysis and trial sequential analysis (TSA), moreover to provide an evidence-based basis for the treatment of PSCI in clinical practice.MethodsThe study conducted a comprehensive search of eight major domestic and international databases, including PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, VIP and China Biology Medicine (CBM). Four English and four Chinese databases of randomized controlled trials of acupuncture combined with rTMS for the treatment of PSCI from inception until July 2025. Systematic reviews and meta-analyses were conducted based on the Cochrane systematic review method by using RevMan5.4 and Stata/MP 18.0, and trial sequential analyses were performed by TSA 0.9.ResultsSixteen RCTs involving 1,058 patients were included, including 532 patients in the experimental group and 526 patients in the control group. Meta-analysis results showed that the experimental group had a higher clinical effectiveness rate in treating patients with PSCI compared to the control group [RR = 1.29, 95% CI (1.08, 1.55), p = 0.005]. The experimental group significantly improved scores on several scales: Montreal Cognitive Assessment (MoCA) [MD = 2.95, 95% CI (2.37, 3.53), p < 0.00001], Mini-Mental State Examination (MMSE) [MD = 2.89, 95% CI (2.13, 3.64), p < 0.00001], LOTCA [MD = 13.61, 95% CI (6.57, 20.65), p = 0.0002], Modified Barthel Index (MBI) [MD = 10.86, 95% CI (7.79, 13.94), p < 0.00001], Activity of Daily Life (ADL) [MD = 15.33, 95% CI (10.06, 20.61), p < 0.00001]. Also it was found to reduced the latency of P300 in the experimental group [MD = −18.18, 95% CI (−25.76, −10.61), p < 0.00001] and prolonged the amplitude of P300 [MD = 1.55, 95%CI (0.71, 2.39), p = 0.0003]. In addition, it could increase the Brain-derived Neurotrophic Factor (BDNF) level in the blood of the patients [MD = 0.93, 95%CI (0.52, 1.35), p < 0.0001], and decrease the Neuron-Specific Enolase (NSE) levels [SMD = −1.26, 95% CI (−1.59, −0.93), p < 0.00001]. There are two studies reported the adverse events. The TSA showed that the cumulative Z value of the meta-analysis of the clinical effectiveness rate, MoCA, and MMSE scales crossed the traditional and TSA boundaries, proving reliable conclusions.ConclusionAcupuncture combined with rTMS can improve cognitive function, regulate daily living ability, and regulate neurotransmitter levels in patients with PSCI, which is worthy recommended in the clinic. However, due to limitations in sample size, inclusion quality and incomplete reporting, it is worth noting that more rigorously designed and high-quality studies are needed to further validate these conclusions.